Strengthening of Self Compact High Strength Concrete Beams with CFRP Wrapping - Pyae, Phyo Pain (Universiti Teknologi PETRONAS, 2018)
Self-compacting concrete (SCC) is a self-flowing concrete that means it does not need vibration and, indeed, should not be vibrated. It uses superplasticisers to significantly increase the ease and rate of flow. It achieves compaction into every part of the mould or formwork simply by means of its own weight without any segregation of the coarse aggregate. However, when adding the steel fibers into the mix design, it reduces the flow ability of Self Compact High Strength concrete. The behavior of self-compact concrete is hard but it is brittle and shows the lower deformation capacity. Therefore, this study investigated the effect of the CFRP (Carbon Fiber Reinforced Polymer) strengthening to the High Strength Self Compact concrete beams without using steel fibers in the mix design. The strengthening for the beams was applied with the variable of a spacing of the strengthening CFRP wrapping. Samples of CFRP reinforced concrete beam were tested to the failure of center point loading after curing 28 days. The results obtained are compared the strengthening of the performance of High Strength Self Compact Concrete beam without wrapping CFRP and with CFRP on using different diameter of reinforcement steel bars.